Utility of transcranial ultrasound in predicting Alzheimer's disease risk - Tomek, Aleš; Urbanová, Barbora; Hort, Jakub (Journal of Alzheimer's disease, 2014)
Alzheimer's disease (AD) is a progressive, neurodegenerative disease characterized by an increasing incidence. One of the pathologic processes that underlie this disorder is impairment of brain microvasculature. Transcranial ultrasound is a non-invasive examination of cerebral blood flow that can be employed as a simple and useful screening tool for assessing the vascular status of brain circulation in preclinical and clinical stages of AD. The objective of this review is to explore the utility of using a transcranial ultrasound to diagnose AD. With transcranial ultrasound, the most frequently studied parameters are cerebral blood flow velocities and pulsatility indices, cerebrovascular reserve capacity, and cerebral microembolization. On the basis of current knowledge, we recommend using as a transcranial Doppler sonography screening method of choice the assessment of cerebrovascular reserve capacity with breath-holding test.
Keywords: kognitivní poruchy; lidé; Alzheimer Disease; Cerebrovascular Circulation; Cognition Disorders; Humans; Ultrasonography, Doppler, Transcranial; ultrasonografie dopplerovská transkraniální; mozkový krevní oběh; Alzheimerova nemoc